Perbandingan Antara Suap dan Gratifikasi Terkait Penerapan Pasal 11 dan Pasal 12B UU TIPIKOR - Faiz Aulia Rahman; Irwan Triadi (CV. Era Digital Nusantara, 2025)
This study examines the legal distinction and application between bribery under Article 11 and gratification under Article 12B of the Indonesian Anti-Corruption Law. Utilizing a qualitative method with a statute approach, the research analyzes statutory definitions and Supreme Court jurisprudence. Significant ambiguity exists due to overlapping elements, necessitating a clear differentiation between transactional bribery and gratification. The findings reveal that bribery requires a